The choice of rational number of transport vehicles in view of the material flow parameters - Галкін, Андрій Сергійович (Technology audit and production reserves, 2013)
The author stresses that in today's market conditions when determining the number and brand of transport vehicles it is necessary to consider the parameters of material flows. Changing the material flow parameters throughout the year raises questions of the choice of the brand and the number of transport vehicles and the appropriateness of using their own and hired transport vehicles. Changing of any parameter of material flow can lead to a change of transportation technology, and hence a change of the type and technical parameters of the vehicle for transportation. Out of the presented parameters of the material flow the conditions of transportation are considered. One of the transportation conditions is temperature control of cargo transportation. This parameter has a significant impact on the transportation of perishable goods. Seasonal ambient temperature is very unstable and impossible to forecast in full; therefore, the transport company, even at a constant volume of material flow should be able to make variations in order to provide the flexibility and adaptability of its activities until the changes in temperature conditions of transportation. The approaches to the formation of a rational number and brand of transport vehicles were considered. On the example of intercity transportation of perishable foods it was found that with constant material flow parameters the change in temperature, which is one of the conditions of transportation, affects: the transportation technological process, choice of the type of the transport vehicle (its technical parameters) and their number.